A Quadricuspid Aortic Valve as Seen by Cardiac Magnetic Resonance Imaging. Issue 9 (1st September 2016) - Jones, James; Liotta, Robert; Hood, Maureen; Bustamante, Alexander
ABSTRACT: We report a case of a 35-year-old active duty male with a rare quadricuspid aortic valve identified via transthoracic echocardiography following the detection of an incidental grade I/VI diastolic murmur. Further characterization of the anatomical findings and aortic valve flow dynamics were evaluated with cardiac magnetic resonance imaging. Accurate assessment of the various valve morphologies is essential, as it guides surgical treatment options to correct the defect. Our case highlights the complimentary role of cardiac magnetic resonance imaging in defining the anatomy and functional consequences of a quadricuspid aortic valve.